The Huawei and Snowden Questions: Can Electronic Equipment from Untrusted Vendors be Verified? Can an Untrusted Vendor Build Trust into Electronic Equipment? - Lysne, Olav (Simula SpringerBriefs on Computing, 2018)
cyber security; IT management; computer science; computer engineering; digital vulnerability